КРИТЕРІЇ ПРОЦЕСУ ФОРМУВАННЯ ЦІННІСНИХ ПЕРЕКОНАНЬ МАЙБУТНЬОГО МУЗИКАНТА-ПЕДАГОГА (Педагогіка вищої та середньої школи, 2007)
The problem of valuable belief of the future musicians-teachers is considered in the article. The criteria cof process of formation of valuable belief are defined there with the purpose of their effective usage in teaching and educational process.